1997
DOI: 10.1002/stem.5530150812
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of hematopoietic stem cells in utero

Abstract: Hematopoietic stem cell (HSC) transplantation in children and adults with congenital lymphohematopoietic disorders is limited by donor availability, graft failure, graft-versus-host disease (GVHD) and delayed immunological reconstitution. These problems may be circumvented by transplanting the patient before birth. Prenatal cellular therapy for the treatment of congenital diseases has tremendous theoretical appeal. Potential advantages of prenatal transplantation include: A) fetal immunologic immaturity and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
48
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 47 publications
2
48
0
1
Order By: Relevance
“…53,54 Transduced CD34 ϩ cells and bone marrow cells from repopulated sheep were plated in MethoCult GF H4435 (StemCell Technologies, Vancouver, BC, Canada) and cultured at 37°C and 5% CO 2 according to the manufacturer's instructions. Individual culture colony-forming units (CFU-Cs) in 20 L medium were withdrawn with a Pipetman into 1 mL PBS (GIBCO).…”
Section: Human Cd34 ؉ Cell Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…53,54 Transduced CD34 ϩ cells and bone marrow cells from repopulated sheep were plated in MethoCult GF H4435 (StemCell Technologies, Vancouver, BC, Canada) and cultured at 37°C and 5% CO 2 according to the manufacturer's instructions. Individual culture colony-forming units (CFU-Cs) in 20 L medium were withdrawn with a Pipetman into 1 mL PBS (GIBCO).…”
Section: Human Cd34 ؉ Cell Transductionmentioning
confidence: 99%
“…The fetal sheep model was chosen for evaluating the engraftment of the most primitive human hematopoietic cells. 53,54 Cotransduced cells representing 9 independent peripheral blood CD34 ϩ -cell collections were transplanted into fetal sheep (5 FeLV-C/ GaLV, 4 RD114/GaLV, including 1 set of twins). DNA was extracted from peripheral blood and bone marrow cells collected from live-born animals between 1 to 9 months after birth for analysis of human hematopoietic-cell engraftment by PCR analysis †Determined by RT-PCR (n ϭ 6).…”
Section: Transduction Of Human Cd34 ؉ Cells With Felv-c-and Rd114-psementioning
confidence: 99%
“…However, the relationship between human CD34 Ϫ and CD34 ϩ stem cells and the role of CD34 Ϫ stem cells in clinical transplantation remain unclear. Xenograft repopulation assays using fetal sheep (7,8) and immune-deficient mice (9,10) were crucial for the identification of human CD34 Ϫ stem cells because Lin Ϫ CD34 Ϫ cells have little or no clonogenic [colony-forming cells (CFC)] or long-term culture-initiating cell (LTC-IC) activity. Using the sheep xenograft model, Zanjani et al showed that Lin Ϫ CD34 Ϫ cells contained stem cells capable of long-term repopulation and multilineage differentiation in vivo (5).…”
mentioning
confidence: 99%
“…9 During this time of rapid expansion of hematopoiesis, donor HSCs might engraft without the need for cytoablative conditioning to provide space for the transplanted HSCs. These hypotheses have been supported by experiments in sheep and other large animals, 8 as well as successes in treating humans with immunodeficiency disorders using IUT. [10][11][12][13] The success of IUT in treating certain immunodeficiencies led us to explore this therapy for the treatment of chronic granulomatous disease (CGD).…”
mentioning
confidence: 86%
“…[1][2][3][4] The proposed advantages of IUT pertain to the immaturity of the fetal immune system and the rapid development of the fetal hematopoietic system. 1,[5][6][7][8] Prior to 14 weeks gestation, the fetal immune system has been presumed to be immature and may allow transplantation of HSCs regardless of major histocompatibility antigen (MHC) disparity. Early in the second trimester, at the time of IUT, hematopoiesis is in a period of continued growth in the liver and colonization of the long bones has begun.…”
mentioning
confidence: 99%